Professores do campo e no campo : um estudo sobre formação continuada e em serviço na Escola Distrital "Padre Fulgêncio do Menino Jesus", no município de Colatina/ES - Gava, Marleide Pimentel Miranda (2011)
How does the continuing education in schools happen? Legally instituted and instituting par excellence, this object highlights and it is a primordial element in the problematization of the research. Who are the subjects of the formation process? Who actually educates whom? Supported on Paulo Freire's conceptions and in dialogues made with Carvalho, Novoa and Brandão, the search for analyzing and understanding the processes of training of professionals from a District school in the city of Colatina, it is consolidated through research engendered in an educational and peasant universe. The choice for a qualitative study based on participant observation provides permanent constructs and reconstructive, extending the look beyond what is visible or "visualized" in the daily school - locus of this research. The urban and the rural are bridge elements in the construction of the training space and in the constitution of the other formative spaces that extrapolate the school environment. Families and communities are fundamental elements to the formation of the students and educators. The professionalization of teachers and the historical and social standardization that configure it conceptually are evidenced. Dialogues, tensions and expectations present themselves in situations experienced by the collectivity and in the moments that search for transforming the District school in an identified school and according to the peasant reality mobilized subjects that began to participate actively in their training pathways